Influence of gender; age, religion and. ethnicity on peer- victimization among; primary four pupils in Ibadan, Nigeria (2006)
Peer-victimization has been found to be a universal phenomenon among children, which can lead to very grave consequences in the emerging adult, This study examined the influence of gender, age, religion and ethnicity on peer-victimization of 240 (131 boys and 109 girls) purposively selected primary 4 pupils in Ibadan metropolis, There was no gender difference in overall peer-victimization of primary school pupils, The Same patternwas observed in age, religion and ethnicity dimensions. It is then concluded that experience of peer victimization cuts across race and culture, its occurrence and dynamics are culturally universal. However, there exist some. Differences that can be attributed to cultural differences. Research efforts thus, should focus more on this area with emphasis on intervention and rehabilitation,